Modulation transfer functions in children: pupil size dependence and meridional anisotropy - Carkeet, Andrew; Leo, Seo-Wei; Khoo, Boo-Kian; Au Eong, Kah-Guan (Investigative ophthalmology & visual science, 2003)
This study quantified preschool children's optical quality in terms of their aberrations and modulation transfer function (MTF), and examined the dependence of MTF on pupil size and grating orientation. Aberrometry was used to measure Zernike coefficients in 34 Chinese preschool children (18 males, 16 females; aged 4.95-6.89 years; mean, 5.91 +/- 0.56). For each subject, after mathematical correction for refractive error, these wavefront errors were used to calculate MTF (lambda = 550 nm) for pupil sizes from 1 to 5 mm and for gratings at orientations in 15 degrees intervals. Aberrations were correlated between right and left eyes, for wavefront RMS and some Zernike coefficients. Average aberrometry results showed that third-order terms predominated, in addition to some positive spherical aberration with an average higher order root mean square (RMS) of 0.20 micro m over a 5-mm pupil. Average MTFs were optimal for 3-mm pupil sizes at lower spatial frequencies (<69 cyc/deg) and slightly better than those found by similar techniques in young adults. Heights of MTFs were significantly related to higher order RMS (Spearman rho = -0.926). MTFs showed a small meridional anisotropy for 3-mm pupils, with average MTF for vertical gratings (horizontal modulation) being slightly, but significantly better than for horizontal gratings (vertical modulation). There was no evidence of an oblique effect in the optics of these children. In these children, ocular optical quality is pupil dependent, shows slight meridional anisotropy and is slightly better than that for young adults.